The role of the 20-hydroxyecdysone (20E) signaling pathway in modulating Anopheles arabiensis reproduction, gut microbiome and anti-bacterial immunity - Ekoka, Elodie (University of the Witwatersrand, Johannesburg, 2023)
The 20-hydroxyecdysone (20E) signaling pathway, which is activated when 20E binds to its ecdysone receptor, EcR, is a promising target to reduce Anopheles mosquitoes’ ability to transmit malaria. The function of this pathway is typically assessed by altering the pathway and assessing how this manipulation affects a phenotype of interest. Two ways to alter this pathway include injecting mosquitoes with 20E or reducing EcR transcript levels with RNA interference (RNAi). Whether the 20E signaling pathway regulates An. arabiensis fecundity, fertility, gut bacteria, and immunity has never been investigated. These questions were addressed in this study by using a South African An. arabiensis strain. First, RNAi was used to investigate whether EcR silencing affects An. arabiensis reproductive output. While EcR depletion did not affect the mosquito fecundity, both vitellogenesis and egg fertility were impaired, as indicated by adecrease in the expression of some yolk genes and the number of eggs that hatched into larvae. Next, a link between the gut bacteria and EcR expression was established, by showing that antibiotic-fed (i.e., with less gut bacteria) mosquitoes displayed fewer EcR transcripts. To investigate whether the relationship between An. arabiensis gut microbiome and EcR expression was mediated by the mosquito innate immune defenses, the expression of ten selected anti-bacterial immune genes was measured in the gut and the whole mosquito after disturbing the 20E signaling pathway. This experiment uncovered that the 20E signaling pathway down-regulates the mosquito anti-bacterial immune defenses, which may favour bacterial proliferation post feeding. Finally, the effect of Gram-negative and Gram-positive bacteria on EcR expression was assessed by injecting mosquitoes with each type of bacteria and quantifying EcR transcripts. The results suggested that only Gram-negative bacteria influenced EcR expression. Altogether, these results demonstrated that An. arabiensis reproduction, gut microbiome, and antimicrobial peptides are regulated by 20E.
A thesis submitted in fulfilment of the requirements for the degree Doctor of Philosophy, to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2023.
Keywords: 20-hydroxyecdysone; Mosquito immunity; Gut microbiome; Vector control; Malaria; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education